Debinding process of ss316L metal injection moulding under argon atmosphere - Jol, P. Jose; Amin, A. M.; Ibrahim, M. H. I.; Zhong, Z.W.; Shamsudin, S. (UNIVERSITI TEKNIKAL MELAKA, 2020)
Solvent and thermal debinding acted as binder in removing Restaurant Waste Lipid (RWL) and Polypropylene (PP) from the stainless steel 316L. This investigation was carried out to determine the effect of thermal debinding variables on density, shrinkage and surface morphology of the brown parts other than to remove the binder from the SS316L under the Argon atmosphere with flow rate of 5 ml/min. The parameter used for solvent debinding process was solvent temperature at 60°C for six hours, while thermal debinding process was conducted at various temperature of 400°C, 500°C and 600°C, heating rate of 10 °C/min, 20 °C/min and 30 °C/min, dwell time of 30 min, 60 min and 90 min, and cooling rate of 5 °C/min, 10 °C/min and 15 °C/min. Analysis of weight loss percentage was done on the brown part after the solvent debinding and thermal debinding processes. Scanning Electron Microscope (SEM) was used to confirm the removal of RWL and PP from the compacts based on the porosity form, and attachment of PP in the powder particles. This investigation showed that debinding parameters were important in terms of their effects on the physical properties. Based on the observation through SEM and consideration of the factors that affected the physical properties of the parts, it was found that RWL was completely extracted out at 60°C for six hours, while the thermal temperature of 500°C with heating rate of 10 °C/min, dwell time of 60 min and cooling rate of 15 °C/min were the optimal thermal debinding parameters in PP removal.